TPACK FRAMEWORK: CHALLENGES AND OPPORTUNITIES IN EFL CLASSROOMS - Taopan, Lita Liviani (Research And Innovation In Language Learning (RILL), 2020)
Technological pedagogical and content knowledge (TPACK) is a dynamic framework for defining teachers' knowledge. This framework is needed for designing, implementing, and evaluating curriculum and instruction with technology. TPACK framework was firstly developed by Shulman (1986) and then expanded by Mishra & Koehler (2006) by adding the technology element. The purpose of this inquiry is to explore and retell the story of an English teacher using the TPACK framework for teaching English. More specifically, the study is intended to know the challenges and the opportunities in using the TPACK framework in teaching English. A narrative inquiry with the thematic analysis used for analyzing the data. To collect the data, the researcher used a semi-structured interview, observation, and document analysis. The participant was an experienced English Teacher in a high school in Indonesia. The study revealed that technology integration in teaching English is quite complicated. The teacher deals with challenges like IT literate, internet connection, and lack of ideas to create meaningful tasks using technology. Otherwise, technology integration offers some opportunities such as a pleasant and flexible classroom, motivate students and teacher to improve themselves and various opportunities to develop the multimodal product. This finding is a useful input related to the EFL research on technology integration.